KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMK DALAM MENYELESAIKAN PERMASALAHAN MATERI SISTEM PERSAMAAN LINIER TIGA VARIABEL (SPLTV) - Ismail, Nizar Mahar Dhika; Hakim, Dori Lukman (Program Studi Pendidikan Matematika, FKIP, Universitas Siliwangi, Tasikmalaya, 2023)
This article discusses the Analysis of Mathematical Problem-Solving Ability in SPLTV material. So get an overview to understand the problem, develop a problem-solving plan, solve the problem, and conduct a review in the given problem-solving process. This research is a qualitative research using descriptive method. The subjects taken were 6 students of class XII SMK in a school in Karawang Regency. The instrument consists of solving the problem of function material which was adopted from the teaching materials of the 2017 revised edition of the curriculum compulsory textbook. The data analysis technique used consists of 3 stages, namely analyzing the results of students' answers, presenting the results of data analysis, and making conclusions from the results of data analysis of students' mathematical problem solving abilities. The result of this article is to provide an overview of solving SPLTV material which is carried out related to everyday problems related to mathematics.